SULAM: CSR for SMK Bandar Perda / Irina Mohd Akhir ... [et al.] - Mohd Akhir, Irina; Abd Rahman, Rabiatul Adawiyah; Mahat, Fadhlina; Johari, Noorsa Riza (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
The Program USR SIRI 1 is a collaboration program between the Faculty of Hotel & Tourism Management (FPHP), Counseling unit and Misi Akademik for Bandar Perda High School’s B40 students that are taking SPM. This program serves as a wonderful platform for knowledge transfer in Corporate Social Responsibility (CSR) that emphasizes student’s motivation through effective communication and engaging practical activities. The primary objective of the CSR program is to introduce students to the captivating and multifaceted world of the hotel and tourism industry. The program aims to equip students with a wide range of valuable practical skills that will be beneficial for their future careers in this dynamic field. SPM'. The program is called ‘Hospitaliti dan Kursus Pengurusan Hotel dan Pelancongan, Santai Minat Kemahiran & Keusahawanan Kursus Pengurusan Hotel & Pelancongan; Intervensi Jurang Status Sosioekonomi (SES) Layak Sijil It is with great pleasure and gratitude that we acknowledge the successful execution of this program at FPHP’s faculty. This accomplishment would not be possible without the unwavering support and dedication of our esteemed partners, ICAN PJI, HEA, the Counsellor Unit, Farm Fresh, and Masjid Daerah Seberang Perai Tengah whom played an instrumental roles in making this collaboration a resounding success.